United Architects of the Philippines achievers : college of fellows - College of Fellows, United Architects of the Philippines; United Architects of the Philippines (Diliman, QC : College of Fellows, United Architects of the Philippines, 2015)
This Achievers book is a compilation of the biographies and lifetime achievements of 80 distinguished members of the College of Fellows and 12 Likha Awardees of the United Architects of the Philippines. These Architects have been the backbone of the profession and the organization through their many years of practice and serving. It is with great pleasure and honour that we feature their siginificant works and invaluable accomplishements.
May I Always Build 1 -- UAP March 1 -- Foreword 4 -- Preface 6 -- Introduction 7 -- College of Fellows -- 2014-2015 Officers -- 2014-2015 Members Jury of Fellows 9 -- Past Chancellors 10 -- Acknowledgments 212
Keywords: ARCHITECTS -- BIOGRAPHY -- PHILIPPINES; ARCHITECTURE -- PHILIPPINES